OPTIMASI TINGKAT PEMBERIAN PAKAN BUATAN TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN PATIN JAMBAL (Pangasius djambal) - Ida Handayani; Erwin Nofyan; Marini Wijayanti (Universitas Sriwijaya, 2014)
ABSTRACT The aim of this research was to know optimal feeding rate for growth, survival rate, food convertion, protein efficiency ratio, protein retention and lipid retention of Pangasius djambal fingerlings (weight 3.5-4.0 g). This experiment was done from Maret until May 2007, at Jambi Freshwater Aquaculture Development Center. This experiment used four treatments at feeding rate 2.50%, 5.00%, 7.50% and 10.00% of fish body weight. The result of research showed that the feeding rate 10.0% of fish body weight gave the highest value for daily growth rate 4.11%. the feeding rate 5.0% of body weight wasn’t different in daily growth rate until 7.50% of fish body weight significantly and gave food cenvertion efficiently until 1.35. The feeding rate 2.50% of fish body weight had the highest value for protein efficiency ratio (2.49), protein retention (153.70%) and lipid retention (175.31%). The optimum feeding rate for daily heavy growth rate were feeding rate 8.88% of fish body weight. The survival rate of P. djambal in this research showed the high percentage that was 100% Keywords: Growth, survival rate, P. djambal, feeding rate